PEMANFAATAN PASTA BUAH MERAH (Pandanus conoideus L) SEBAGAI BAHAN SUBSTITUSI TEPUNG KETAN DALAM PEMBUATAN DODOL - . Murtiningrum; Isak Silamba (JURNAL AGROTEKNOLOGI, 2010)
The objectives of the research are to obtain the best “dodol” formulation of by using red fruit pasta as substitution ingredient of waxy rice flour, and to know its physicochemical electrophoresis properties and panelist preferences. The ratios between red fruit paste and waxy rice flour used in “dodol” preparation were 1,75:1; 1: 1; 1:1,75 and 1:2,5 (w/w). The result indicated that the best ratio of formulation of “dodol” was 1,75:1. The preferences test showed that the panelist like and texture of the formulation slightly color and odor. The increase of the use red fruit paste will produce delicious good odor non-sticky “dodol”, also increase panelist preferences. The best formulation of “dodol” have firmness value of 512,15 gf, elasticity 0,33 %, stichness 275,38 gf, water activity 0,87, water content 34,24 % and total solid 65,76 %.Keywords: “dodol”, psychochemical electrophoresis, red fruit pasta